Wine-making with Protection of Must against Oxidation in a Warm, Semi-arid Terroir - Corona, O. (South African Journal of Enology and Viticulture, 2010)
To protect varietal aromas from oxidation before alcoholic fermentation, two grape must samples were prepared from white grapes potentially low in copper, pre-cooled and supplemented with ascorbic acid and solid CO2 (trial ACO2) or SO2 (trial BSO2). The wines prepared from musts protected from oxidation had aroma descriptors that included “passion fruit” and “grapefruit skin”. The lower concentrations of flavanols in the ACO2 trial demonstrated that the use of solid CO2 as an oxidation preventative instead of SO2 reduced the extraction of these polyphenols from the grape solids. The higher concentration of hydroxycinnamoyl tartaric acids of the wine from the A CO2 trial with respect to BSO2 was ascribed to the lower grape polyphenoloxidase activity induced by the lower oxygen level in the A CO2 trial, or to the combination of caftaric acid quinone with the SO2 in B SO2. Although the grapes were very ripe (alcohol in wines ~ 14.5% vol), the wines made with musts prepared by the two techniques were characterised by aroma descriptors like “passion fruit” and “grapefruit skin”, and these aromas were not detected in the wines prepared from unprotected musts.